Modification and superhydrophilization of electrospun polyvinylidene fluoride membrane using graphene oxide-chitosan nanostructure and performance evaluation in oil/water separation. Issue 5 (October 2021) - Mehranbod, Nasir; Khorram, Mohammad; Azizi, Samaneh; Khakinezhad, Naghmeh
Abstract: Surface properties of fish scales have inspired many research works aiming at fabrication of membranes with specific surface wettability that have been applied vastly for treating oily wastewater. The goal of this study was wettability modification of an electrospun nanofibrous membrane based on polyvinylidene fluoride (PVDF) to make it an effective filtering media for the field of oil-water separation. Surface modification of highly hydrophobic PVDF membrane was performed by coating it with chitosan–graphene oxide nanostructures. The modified membrane acquired superhydrophilicity and underwater superoleophobicity properties. Characteristics of the membrane were determined and analyzed using SEM, FT-IR, XRD, AFM and EDX. Contact angle measurements were used to determine membrane wettability. The fabricated membrane showed zero water contact angle and a maximum oil contact angle of 154°. The modified membrane was tested for separation of some oil/water mixtures under different operating conditions. The measured flux of oil/water mixtures in these tests ranged from 30, 120 ± 1154 to 33, 637 ± 1328 average of 31, 673 ± 1447 L m − 2 h − 1 bar − 1 under 0.4 bar pressure difference. The test results revealed excellent oil separation efficiency up to 99% and, superior antifouling properties with no significant change in several cycles of oil/water mixtures separation. Furthermore, the modified membrane could effectively separate oil/water mixtures in a broad pH range and could be used with a high flux recovery ratio. Graphical Abstract: ga1 Highlights: Hydrophobic electrospun PVDF nanofibers were transformed into a superhydrophilic and underwater superoleophobic membrane. The modified membrane separated the oil/water mixture with high separation efficiency. Coated PVDF membrane had lower irreversible fouling resistance and higher flux recovery ratio compared to pristine PVDF membrane. The modified membrane had good anti-fouling property and stability in harsh conditions.